The Atacama Cosmology Telescope: The Two-season ACTPol Sunyaev–Zel’dovich Effect Selected Cluster Catalog - Hilton, Matt; Hasselfield, Matthew; Sifón, Cristóbal; Battaglia, Nicholas; Aiola, Simone; Bharadwaj, V.; Bond, J. Richard; Choi, Steve K.; Crichton, Devin; Datta, Rahul; Devlin, Mark J.; Dunkley, Joanna; et al. (The Astrophysical Journal Supplement Series, 2018)
We present a catalog of 182 galaxy clusters detected through the Sunyaev-Zel'dovich (SZ) effect by the Atacama Cosmology Telescope in a contiguous 987.5 deg2 field. The clusters were detected as SZ decrements by applying a matched filter to 148 GHz maps that combine the original ACT equatorial survey with data from the first two observing seasons using the ACTPol receiver. Optical/IR confirmation and redshift measurements come from a combination of large public surveys and our own follow-up observations. Where necessary, we measured photometric redshifts for clusters using a pipeline that achieves accuracy Δz/(1 + z) = 0.015 when tested on Sloan Digital Sky Survey data. Under the assumption that clusters can be described by the so-called universal pressure profile (UPP) and its associated mass scaling law, the full signal-to-noise ratio > 4 sample spans the mass range , with median . The sample covers the redshift range 0.1 < z < 1.4 (median z = 0.49), and 28 clusters are new discoveries (median z = 0.80). We compare our catalog with other overlapping cluster samples selected using the SZ, optical, and X-ray wavelengths. We find that the ratio of the UPP-based SZ mass to richness-based weak-lensing mass is . After applying this calibration, the mass distribution for clusters with M 500c > 4 1014 M o is consistent with the number of such clusters found in the South Pole Telescope SZ survey